Transcatheter Closure of Patent Ductus Arteriosus in Elderly Patients: Initial and One-Year Follow-Up Results—Do We Have the Proper Device? - Michal Galeczka; Malgorzata Szkutnik; Jacek Bialkowski; Sebastian Smerdzinski; Mateusz Knop; Adam Sukiennik; Roland Fiszer (Journal of Interventional Cardiology)
Objectives. Patent ductus arteriosus (PDA) in elderly patients is an uncommon anomaly, and the duct itself is often calcified and fragile; therefore, transcatheter closure is more difficult. The aim is to analyse periprocedural and one-year follow-up results of transcatheter closure of PDA in such patients. Methods and results. Retrospective analysis of 33 elective patients aged ≥55 years (median 63; 56–85; 29 women), in whom PDA was closed percutaneously between 2002 and 2018 in two tertiary centres. All but three patients were symptomatic, with most in NYHA II (n = 14) and III (n = 11) class; pulmonary hypertension (n = 22), arterial hypertension (n = 22), duct calcifications (n = 17), atrial fibrillation (n = 15), significant mitral regurgitation (n = 5), and decompensated renal failure (n = 2) were observed. Different devices were applied depending on PDA morphology; nitinol wire mesh occluders with symmetrical articulating discs have been the most used in recent years (n = 11). Follow-up was conducted at an outpatient clinic (28/33 patients). The procedure was successful in all patients. There was one embolisation, followed by implantation of a larger device. No major complications were noted. A small residual shunt was present in echocardiography in one patient after one year. NYHA class improved in all but two patients (with multiple comorbidities). Conclusions. Transcatheter PDA closure in elderly patients is safe and efficient with a high complete closure rate and few complications. Amplatzer duct occluder type II is an attractive device in such patients.